1989
DOI: 10.1021/j100346a043
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field effects on the intra- and intermolecular exciplex fluorescence of phenanthrene and dimethylaniline

Abstract: As noted earlier, the equilibrium between FeDTPA2" and FeDTPA-OFI3" is slow and, therefore, it is unlikely that normal ligand exchange is involved. It is known that Fem can expand its coordination sphere from 6 to 7 and we might speculate that OH" occupies a coordination site that is otherwise available for attack by the DTPA radical.As pointed out previously, on the time scale of the experiment the DTPA radical has not quantitatively converted to its final form (generally considered as a methylene radical of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…29,30,54,55,58,6365 In contrast to that, many studies focusing predominantly on photochemical aspects can be found, suggesting that the exciplex is the initial quenching product even at fairly high permittivities. 28,57,66,67 …”
Section: Introductionmentioning
confidence: 99%
“…29,30,54,55,58,6365 In contrast to that, many studies focusing predominantly on photochemical aspects can be found, suggesting that the exciplex is the initial quenching product even at fairly high permittivities. 28,57,66,67 …”
Section: Introductionmentioning
confidence: 99%
“…As the concentration increases, the magnitude of the field-induced quenching of the LE fluorescence becomes larger, indicating that the intermolecular PIET from DMA to the excited state of PHE is also enhanced by F. The field effect on the intermolecular PIET is also considered to result from the field-induced change in free energy gap. Both the PIET rate ∆I F (ν) ) (fF) 2 C ) (∆µ) 2 [5 +(3 cos 2 -1)(3 cos 2 -1)]/(30h 2 c 2 ) (8) ∆µ ) |∆µ|; ∆R j ) ( 1 / 3 )Tr(∆r) (9) and its field-induced change increase exponentially, as the donor-acceptor distance decreases. It is considered that a radical ion pair is produced following PIET, and then the fluorescent exciplex is produced.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 Phenanthrene chromophores act as an electron acceptor (A), and N,N-dimethylaniline chromophores act as a donor (D) in PIET. 16 Samples for the measurements of the electric field effects on absorption and emission spectra were prepared in the same manner as reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…The charge-separated biradical formed after photoexcitation in benzene can be characterized as an exciplex or a contact ion pair (18) and, therefore, the interradical distance must be very small. The observation of pronounced magnetic field effects suggests a large separation (21 nm) between the two unpaired electrons (3,15). It is reasonable to assume a neutral biradical as a reaction intermediate in benzene.…”
Section: Solvent Effects and Reaction Mechanism Of Photochemistry Ofmentioning
confidence: 99%